Spectral mapping method based on intervals of comonotonicity for modelling of radiative transfer in non-uniform gaseous media. (May 2019) - André, Frédéric; Solovjov, Vladimir P.; Webb, Brent W.; Galtier, Mathieu; Dubuisson, Philippe
Highlights: The concept of interval of comonotonicity is introduced. Over these spectral intervals, the Ck/CKD methods of gas radiation are exact. The technique to build intervals of comonotonicity is described. The method is simple, general and robust. Its accuracy is assessed against LBL calculations in non-uniform situations. ABSTRACT: The aim of this work is to describe a Spectral Mapping Method (SMM) to split spectral intervals into smaller sets of wavenumbers, called intervals of comonotonicity, over which gas spectra in distinct states are rigorously linked through a strictly increasing function. Over small intervals of comonotonicity, the proposed method becomes, in theory, exact. The step-by-step process of construction of intervals of comonotonicity is described and explained. The present work focuses on the two-cell problem. Despite its full generality for the treatment of the blurring effect in k -distribution approaches, the strength of the method is illustrated: 1/ with a high number of subintervals on an IR signature configuration, widely recognized as among the most challenging in band model theory; 2/ with only two subintervals, in a highly non-uniform two-cell configuration. Comparisons with reference Line-By-Line calculations and a mapping technique founded on a scaled map illustrate its relevance for radiative heat transfer and spectroscopic applications.